PENGARUH NISBAH BAGI HASIL TERHADAP PENYALURAN PEMBIAYAAN MUDHÂRABAH - Yayat Rahmat Hidayat (Jurusan Akuntansi Politeknik Negeri Bandung, 2016)
Abstract: This research is motivated by low mudaraba financing in Islamic banking in Indonesia compared with other financing. The financing in Islamic banking in Indonesia is dominated by debt-based financing products for the consumer sector. Though mudaraba financing based finance working capital for the productive sector so as to increase the level of public welfare distribution. So, necessary to find the factors that influence the distribution of Mudaraba Financing. The research method used is quantitative research method. Objects in this study is the profit sharing ratio and mudaraba financing. This research is explanatory research. It was said, because this study connects several variables. Data collection techniques used were Archival Research, because the data used in this research is secondary data derived from SPI and SPS. The analytical tool used is regression analysis aimed at finding the effect of one variable to another variable. The results of this study indicate that profit sharing ratio has a negatively affects the distribution Mudaraba Financing at 91.65% Keywords: Profit Sharing Ratio, Mudaraba Financing, Income